Man and Dog in 20th Century Prose - Pikhartová, Aneta (Univerzita Pardubice, 2025)
This thesis looks at man and dog the 20th century prose. It uses the field of Animal Studies and its various concepts in order to analyze the portrayal of dogs and human-dog relationships in the selected works of fiction. These works include The Call of the Wild and White Fang by Jack London, Where the Red Fern Grows by Wilson Rawls, The Incredible Journey by Sheila Burnford, The Plague Dogs by Richard Adams, and Kävik the Wolf Dog by Walt Morey.
Člověk a pes v próze 20. století
Keywords: animal studies; psi; antropocentrismus; vztah člověka a psa; animal studies; dogs; anthropocentrism; human-dog relationships